2021
DOI: 10.5888/pcd18.200567
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial to Improve Adherence to Follow-up Eye Examinations Among People With Glaucoma

Abstract: What is already known on this topic? Nonadherence to follow-up eye care is common among people with glaucoma and other eye diseases. Use of patient navigators and social workers can increase adherence to eye care appointments. What is added by this report?The results of a randomized, controlled trial of patients with glaucoma and other eye diseases showed that a patient navigation and social work intervention doubled the rate of follow-up adherence in community settings.What are the implications for public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Assistance from patient navigators has led to improved health outcomes in fields such as cardiology [ 55 ] and women’s health [ 56 ]. In ophthalmology, a community-based study found that use of a patient navigator improved appointment follow-up rates after screening for glaucoma [ 57 ]. Similarly, a social worker intervention in eye clinic settings effectively addressed barriers for most patients and reduced patient distress [ 58 , 59 ].…”
Section: How Ophthalmologists Can Take Action To Address Social Needsmentioning
confidence: 99%
“…Assistance from patient navigators has led to improved health outcomes in fields such as cardiology [ 55 ] and women’s health [ 56 ]. In ophthalmology, a community-based study found that use of a patient navigator improved appointment follow-up rates after screening for glaucoma [ 57 ]. Similarly, a social worker intervention in eye clinic settings effectively addressed barriers for most patients and reduced patient distress [ 58 , 59 ].…”
Section: How Ophthalmologists Can Take Action To Address Social Needsmentioning
confidence: 99%
“…While real-world studies, such as the VISIONARY study, provide an important opportunity to examine the treatment outcomes achieved in routine clinical practice, this type of study is associated with a number of limitations. Patients were able to leave the study without providing a reason, and attendance at follow-up appointments also represents a major challenge for ophthalmologists in clinical practice [ 42 ]. Patients were only mandated to attend study visits at baseline and Month 6, meaning that fewer patients attended interim visits at Weeks 4 and 12, and this is reflected in the data reported at these timepoints.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Lancet Global Health Commission on Global Eye Health, women, rural populations, and racial/ethnic minority groups are more likely to have vision impairment, a pervasive inequality that needs to be addressed ( 40 ). This PCD collection on advancing health equity and reducing health disparities concludes with a research study by Leiby et al investigating the effectiveness of an enhanced intervention among people with glaucoma: using patient navigators and social workers to improve patient adherence to follow-up eye care in community settings ( 20 ). The study compared the intervention group with a group of patients in usual care.…”
mentioning
confidence: 99%
“…A Randomized Trial to Improve Adherence to Follow-up Eye Examinations Among People With Glaucoma ( 20 )…”
mentioning
confidence: 99%